Perencanaan Dan Pengorganisasian Dalam Manajemen Pendidikan - Siti Aisyah; Sofie Ahmira Rehgita Br Tarigan; Wahyuni Dazura; Lisna Marselina; Inom Nasution (Journal Innovation In Education, 2024)
Achieving educational goals at school is greatly influenced by student factors. All activities in schools are aimed at students and the existence of students plays a role as a subject as well as an object in the educational process at school. Planning and organizing in educational management is very important and is needed to achieve a better education for the future of the nation's children, therefore The goal of education must be prioritized. If there is unity of strength from various system elements to achieve goals in the institution or organization, then management is considered successful. The approach used is a qualitative approach with a multi-case study design. Data collection techniques were carried out through: observation, documentation and in-depth interviews. The results of the research indicate that student planning should be prepared as early as possible at the beginning of each school year. Planning and organizing students starts from grouping classes based on test results so that superior classes are formed and target classes are formed. Then the principal gives responsibility and authority to the homeroom teacher to develop and direct the students.